2023
DOI: 10.7759/cureus.37734
|View full text |Cite
|
Sign up to set email alerts
|

Libman-Sacks Endocarditis With Triple Valvular Involvement

Abstract: Systemic lupus erythematosus (SLE) is a systemic inflammatory autoimmune disease with a broad spectrum of clinical manifestations. Libman-Sacks endocarditis (LSE) is due to sterile vegetations that arise in association with SLE. Nonbacterial thrombotic endocarditis, also known as marantic endocarditis, Libman-Sacks endocarditis, and verrucous endocarditis, is linked to a number of illnesses, the most prevalent of which is advanced cancer. Most often, the surfaces of mitral and aortic valves are involved. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…LSE can cause formation of large or small clumps of platelets that cause blocking of blood vessels in the brain. 12 These findings are especially significant as the presence of cerebrovascular disease, including TIA, seizures or stroke, in SLE is associated with higher rates of illness and death. Roldan et.al reported that LSE was linked to higher death rates due to its association with embolic CVD and cardiac valvular dysfunction which necessitated high-risk surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…LSE can cause formation of large or small clumps of platelets that cause blocking of blood vessels in the brain. 12 These findings are especially significant as the presence of cerebrovascular disease, including TIA, seizures or stroke, in SLE is associated with higher rates of illness and death. Roldan et.al reported that LSE was linked to higher death rates due to its association with embolic CVD and cardiac valvular dysfunction which necessitated high-risk surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Libman-Sacks endocarditis is a cardiac manifestation of Lupus, first described in 1924 in 4 patients with sterile aortic vegetations [ 3 ]. Its prevalence ranges from 0.9 % to 16 %, without gender preference, in a population aged between 40 and 80 years [ 4 ]. However, this may be underestimated: postmortem studies have found a prevalence of 30 % in a population of SLE sufferers [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is poorly understood: the classic lesion is a verrucous vegetation that develops from an immunologically-induced endothelial lesion leading to the formation of fibrin, platelets and immune complexes on the valve, causing fibrosis and valve dysfunction [ 4 ]. Diagnosis is made on TTE, which shows vegetations with specific characteristics: they are mobile, elongated, narrow-based, with irregular borders and well attached to the valve surface [ 2 ].…”
Section: Discussionmentioning
confidence: 99%